2017
DOI: 10.1002/bse.1948
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Green Initiatives and Green Performance on Financial Performance in the US

Abstract: Sustainable development has received increasing attention in recent literature, driven by increased environmental concerns. We study the influence of green initiatives and green performance on financial performance for the top 500 publicly traded companies in the USA by industry sector. Green initiatives are measured using the concepts Green Pay Link, Sustainability Themed Committee and Audit. Green performance is measured using Energy Productivity, Carbon Productivity, Water Productivity, Waste Productivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 85 publications
9
86
0
Order By: Relevance
“…The results of this study also complement findings reported by Wu and Pagell () and Li, Ngniatedema, and Chen () suggesting that the financial benefits of GSCM practices accrue only in the long term. The Leaders might see GSCM as a future differentiation advantage (Colicchia et al, ), even if it could mean increasing costs in the short term.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study also complement findings reported by Wu and Pagell () and Li, Ngniatedema, and Chen () suggesting that the financial benefits of GSCM practices accrue only in the long term. The Leaders might see GSCM as a future differentiation advantage (Colicchia et al, ), even if it could mean increasing costs in the short term.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the practice of assurance and study of its determinants and effects on CSR reports is emerging (De Beelde & Tuybens, ; Kolk & Perego, ). Other streams of research focus on financial benefits and link managerial green behaviors (e.g., sustainability leadership, environmental performance, and environmental audit) with firm profitability (Ferrón Vílchez & Darnall, ; Kumar, Boesso, & Michelon, ; S. Li, Ngniatedema, & Chen, ; Madsen & Ulhøi, ; Trumpp & Guenther, ), economic value relevance (K. H. Lee, Park, Song, & Yook, ; Miralles‐Quiros, Miralles‐Quiros, & Arraiano, ; Yadav, Han, & Kim, ), analyst forecasts, and corporate reputation (Cormier & Magnan, ; Zou, Zeng, Zeng, & Shi, ).…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
“…In this vein, future studies could also delve into particular relationships between other environmental topics and product portfolio management. The environmental topics that could be developed further include eco‐efficiency initiatives (Li et al , ), green employee behavior (Delgado‐Márquez & Pedauga, ), eco‐innovation (Dangelico et al , ), carbon performance (Giannarakis et al , ), low carbon products (Liu et al , ), green supply chain management (Zhu et al , ) and green supplier selection (Dou et al , ).…”
Section: Resultsmentioning
confidence: 99%